REVITALISASI PERAN DAN FUNGSI DEWAN PENGAWAS DI LEMBAGA KEUANGAN SYARI’AH KOTA METRO - Fatarib, Husnul (El -Hekam, 2017)
The theme of this article Revitalization Role and Function of the Supervisory Board on Financial Institutions Sharia. The author takes a number of BMT Background City Metro WITH stressed Study on Existence penela'ahan Shari'ah supervisory board (DPS) in LKS Metro City, especially in BMT. Further Analysis From this paper will serve to the Reader ABOUT shown a serious issue in LKS That led DPS Metro City And yet functioning Operates Good NOT include: sebahagian BMT Metro City and is NOT yet have a Shari'ah supervisory board (DPS); DPS management yet meet the criteria and standards The ideal; DPS Only the ADA and is domiciled in BMT parent, while the Institute Branch OR BMT under its assistance does NOT have the DPS and no less interesting, in Section Final Research singer, will encounter a number of alternative solution and implementable WITH presenting models Empowerment Model DPS in the Coming include: DPS organizing focused and united on the level of districts and cities, and not in BMT OR ANY syari'ah The ADA Financial Institutions; Institutional Strengthening DPS WITH MECHANISMS juridical and cooperation; Model establishment of monitoring instruments and Evaluation of the boarding costs at the Local Level By DPS DPS Center (DSN-MUI); The role of the region is to maximize ASBISINDO WITH Build Cooperation All integrative And interkonektif; establish criteria and qualiï¬cation of candidate MEMBERS DPS; establish criteria and qualiï¬cation of candidate MEMBERS DPS; MAKE program routine / Periodic for a review to evaluate and monitor the boarding costs DPS in EVERY BMT in the area is the DSN-MUI By Yang is in the central level.